2012
DOI: 10.1371/journal.pmed.1001180
|View full text |Cite
|
Sign up to set email alerts
|

Association between Clean Delivery Kit Use, Clean Delivery Practices, and Neonatal Survival: Pooled Analysis of Data from Three Sites in South Asia

Abstract: A pooled analysis of data from three studies in South Asia demonstrates an association between use of clean delivery kits during home births and reduced risk of neonatal mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 17 publications
2
74
0
Order By: Relevance
“…Our study found that clean cord care practices were associated with more than a third lower neonatal mortality in rural India and adds empirical strength to previous literature which suggests that most neonatal deaths in India and other developing countries are preventable through interventions that have been proven efficacious 10 14 19 20 21…”
Section: Discussionsupporting
confidence: 67%
“…Our study found that clean cord care practices were associated with more than a third lower neonatal mortality in rural India and adds empirical strength to previous literature which suggests that most neonatal deaths in India and other developing countries are preventable through interventions that have been proven efficacious 10 14 19 20 21…”
Section: Discussionsupporting
confidence: 67%
“…Another review by Hundley et al [220] discussed that the levels of birth kit use vary considerably (8-99%) in more than 50 low resource countries; with higher levels being reported where birth kits are distributed free as part of a research program. A recent review of three community-based RCTs carried out between 2000 and 2008 in India, Bangladesh, and Nepal found that each additional clean delivery practice (using a plastic sheet during delivery, a boiled blade to cut the cord, a boiled thread to tie the cord, and antiseptic to clean the umbilicus) was associated with a 16% relative reduction in neonatal mortality (OR 0.84, 95% CI: 0.77 to 0.92) [221].…”
Section: Provision Of Clean Delivery Kitsmentioning
confidence: 99%
“…A study from 2000 to 2008 found the use of safe delivery care kit effective in reducing neonatal mortality, sepsis and other postnatal infections in Nepal, India and Bangladesh[18]. …”
Section: Introductionmentioning
confidence: 99%